Pregnancy after the age of 40 – a new norm in obstetrics - Witek, A.; Bojdys-Szyndlar, Monika (Menopause Review/Przegląd Menopauzalny, 2006)
The recently observed trend of late maternity has been shaped by the change in the women’s outlook on life and thus their consequent independence from the social rules. In the old days the age of 35 was regarded to be the limit of safe maternity. Nowadays, however, this limit is shifted to the age of 40, and further. The probability of complications (such as miscarriage, chromosome abnormality, hypertension induced by pregnancy, diabetes of pregnant women and dead birth) rises with the age of the mother. However, the changing social and demographic trends will constantly increase the number of patients deciding for late pregnancy. Taking into account the risk of such pregnancy, it seems necessary to treat that group of women as „New” norm in obstetrics.